Early Mechanical Failures of the Synthes Variable Angle Locking Distal Femur Plate. Issue 1 (January 2016) - Tank, Jason C.; Schneider, Prism S.; Davis, Elizabeth; Galpin, Matthew; Prasarn, Mark L.; Choo, Andrew M.; Munz, John W.; Achor, Timothy S.; Kellam, James F.; Gary, Joshua L.
Abstract : Objectives: To document the high failure rate of a specific implant: the Synthes Variable Angle (VA) Locking Distal Femur Plate. Design: Retrospective. Setting: Urban University Level I Trauma Center. Patient/Participants: All distal femur fractures (OTA/AO 33-A, B, C) treated from March 2011 through August 2013 were reviewed from our institutional orthopaedic trauma registry. Inclusion criteria were fractures treated with a precontoured distal femoral locking plate and age between 18 and 84. Exclusion criteria were fractures treated with intramedullary nails, arthroplasty, non-precontoured plates, dual plating, or screw fixation alone. The population was divided into 3 groups: less invasive stabilization system (LISS) group (n = 21), treated with LISS plates (Synthes, Paoli, PA); locking condylar plates (LCPs) group (n = 10), treated with LCPs (Synthes, Paoli, PA); and VA group (n = 36), treated with VA distal femoral LCPs (Synthes, Paoli, PA). Average age was 54.6 ± 17.5 years. Intervention: Open reduction internal fixation with one of the above implants was performed. Main Outcome Measures: The patients were followed radiographically for early mechanical implant failure defined as loosening of locking screws, loss of fixation, plate bending, or implant failure. Results: There were no statistically significant differences between groups for age, gender, open fracture, mechanism of injury, or medial comminution. There were 3 failures (14.3%) in group LISS, no failures (0%) in group LCP, and 8 failures (22.2%) in group VA. All 3 failures in group LISS were in A-type fractures (2 periprosthetic) and all failures in group VA were in C-type fractures. When all fractures for all 3 groups were compared for failure rate, there was no statistically significant difference ( P = 0.23). However, when only 33-C fractures were compared, there was significantly greater failure rate in the VA group ( P = 0.03). The mean time to failure in group VA was 147 days (range 24–401 days) and was significantly earlier ( P = 0.034) when compared with group LISS (mean 356 days; range 251–433 days). Conclusions: Early mechanical failure with the VA distal femoral locking plate is higher than traditional locking plates (LCP and LISS) for OTA/AO 33-C fractures. We caution practicing surgeons against the use of this plate for metaphyseal fragmented distal femur fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.